REACTION OF HEPATIC CELLS IN CHILDREN WITH ACUTE INTESTINAL INFECTIONS THAT OCCURRED WITH THE DEVELOPMENT OF TOXICOSIS WITH EXICOSIS - Галина Ивановна Выходцева; Евгения Юрьевна Киричёк; Ольга Петровна Морозова; Людмила Ивановна Зиновьева; Ольга Ивановна Колесникова; Валерий Николаевич Сероклинов (The Publishing House Medicine and Enlightenment, 2023)
The aim of the research - to determine the indicators of cytolysis in a biochemical blood test (BBT) in children with AII that occurred with the development of toxicosis with exicosis of I (AII with TE I) and II degree (AII with TE II). Materials and methods. The study included 135 children aged from 2 months to 6 years with clinical and laboratory manifestations of AII with TE. The patients underwent a BBT study to determine the levels of alanine aminotransferase (AlAT), aspartate aminotransferase (AsAT), alkaline phosphatase (ALP), g-glutamyltranspeptidase (GGT), lactate dehydrogenase (LDH). The results of the study. There was a statistically significant increase in the levels of GGT (p = 0.0293) and LDH (p = 0.00004) among children with AII with TE I up to 1 year, and more often an increase in the level of ALP (p = 0.0322). In children from 1 to 3 years of age, higher levels of alkaline phosphatase (p = 0.0048) and LDH (p = 0.0062) were recorded, and more often - an increase in LDH (p = 0.0068). In the group from 3 to 6 years, the level of GGT was recorded higher (p = 0.0214). There was a statistically significant increase in the levels of AlAT (p = 0.0107), AsAT (p = 0.0037), ALP (p = 0.0050), GGT (p = 0.0080) and LDH (p = 0.0027) among children with AII with TE II up to 1 year. In children from 1 year to 3 years - an increase in the levels of AlAT (p = 0.0117), AsAT (p = 0.0022), ALP (p = 0.0358) and LDH (p = 0.0051), and more often - an increase in the levels of AlAT (p = 0.0269), AsAT (p = 0.0305), GGT (p = 0.0022) and LDH (p = 0.0019). Among children from 3 to 6 years of age, there was an increase in the level of AsAT (p3-1 = 0.0389). Among children with AII with TE II, the LDH level was recorded statistically significantly higher (p = 0.0407). Conclusion. In children, the course of AII with TE was accompanied by a reaction of hepatic cells in the form of cytolytic syndrome. At the same time, these changes depended on the age of patients and the severity of the course of AII, and did not depend on the etiological structure of AII.